Use of plastic waste in bituminous mixes by wet and dry methods. Issue 2 (19th October 2018) - Mishra, Brajesh; Gupta, Mohit Kumar
Abstract : The disposal of plastic waste is a great dilemma in present times due to its non-biodegradable nature and the scarcity and unsustainability of landfills. Studies reveal that it can be successfully utilised in bituminous concrete (BC) mixes in flexible pavements. There are two methods available, namely, dry method (DM) and wet method (WM) that incorporate plastic wastes in the BC mixes. In this study, a comparison has been made by utilising shredded plastic waste carry bags made of low-density polyethylene in BC mixes in flexible pavements by WM and DM. The Marshall stability value, flow value, indirect tensile strength tests were carried out and the results were compared. It was found that DM is the most effective and is a better option as it is simple, economical, eco-friendly and yields better results.